(x+2i)(x-2i)(x+4)=0

Simple and best practice solution for (x+2i)(x-2i)(x+4)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+2i)(x-2i)(x+4)=0 equation:


Simplifying
(x + 2i)(x + -2i)(x + 4) = 0

Reorder the terms:
(2i + x)(x + -2i)(x + 4) = 0

Reorder the terms:
(2i + x)(-2i + x)(x + 4) = 0

Reorder the terms:
(2i + x)(-2i + x)(4 + x) = 0

Multiply (2i + x) * (-2i + x)
(2i * (-2i + x) + x(-2i + x))(4 + x) = 0
((-2i * 2i + x * 2i) + x(-2i + x))(4 + x) = 0

Reorder the terms:
((2ix + -4i2) + x(-2i + x))(4 + x) = 0
((2ix + -4i2) + x(-2i + x))(4 + x) = 0
(2ix + -4i2 + (-2i * x + x * x))(4 + x) = 0
(2ix + -4i2 + (-2ix + x2))(4 + x) = 0

Reorder the terms:
(2ix + -2ix + -4i2 + x2)(4 + x) = 0

Combine like terms: 2ix + -2ix = 0
(0 + -4i2 + x2)(4 + x) = 0
(-4i2 + x2)(4 + x) = 0

Multiply (-4i2 + x2) * (4 + x)
(-4i2 * (4 + x) + x2(4 + x)) = 0
((4 * -4i2 + x * -4i2) + x2(4 + x)) = 0
((-16i2 + -4i2x) + x2(4 + x)) = 0
(-16i2 + -4i2x + (4 * x2 + x * x2)) = 0
(-16i2 + -4i2x + (4x2 + x3)) = 0
(-16i2 + -4i2x + 4x2 + x3) = 0

Solving
-16i2 + -4i2x + 4x2 + x3 = 0

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '-4x2' to each side of the equation.
-16i2 + -4i2x + 4x2 + -4x2 + x3 = 0 + -4x2

Combine like terms: 4x2 + -4x2 = 0
-16i2 + -4i2x + 0 + x3 = 0 + -4x2
-16i2 + -4i2x + x3 = 0 + -4x2
Remove the zero:
-16i2 + -4i2x + x3 = -4x2

Add '-1x3' to each side of the equation.
-16i2 + -4i2x + x3 + -1x3 = -4x2 + -1x3

Combine like terms: x3 + -1x3 = 0
-16i2 + -4i2x + 0 = -4x2 + -1x3
-16i2 + -4i2x = -4x2 + -1x3

Reorder the terms:
-16i2 + -4i2x + 4x2 + x3 = -4x2 + 4x2 + -1x3 + x3

Combine like terms: -4x2 + 4x2 = 0
-16i2 + -4i2x + 4x2 + x3 = 0 + -1x3 + x3
-16i2 + -4i2x + 4x2 + x3 = -1x3 + x3

Combine like terms: -1x3 + x3 = 0
-16i2 + -4i2x + 4x2 + x3 = 0

The solution to this equation could not be determined.

See similar equations:

| 6=J-5 | | 3y+7=2x-5 | | N/10-20=20 | | 100x-40y=320 | | 6x7/8= | | 3z+5z=0.6 | | (n)(n)+72=-17n | | 3x-5=6+x | | 6x+7=3(2x+4) | | (k)(k)-11k+30=0 | | (12y)(12y)+40y=7 | | 3x^2-8+5x=0 | | 3x+6=507 | | 10/3x1/2 | | 6d+4=-32 | | 5/6z=5/7 | | 18/sin40 | | a=bd | | p^2-14p=51 | | (d)(d)=5d | | 10c/2-32/4=56/8 | | (w)(w)=12 | | 3/7x1/7 | | 6-9(1-7n)=-21 | | -4x-16y=-12 | | 2y=-5x-3 | | (2x+8)+(3x-4)+x= | | 8(x+9)=72 | | 3y-10+y+y-10=180 | | (3b)(3b)+7b-6=0 | | x=(2x+8)+(3x-4)-x | | m(m-3)-2m(m-4)=-(m^2-4m)6 |

Equations solver categories